Binding of Red Clover Isoflavones to Actin as A Potential Mechanism of Anti-Metastatic Activity Restricting the Migration of Cancer Cells - Budryn, Grażyna; Grzelczyk, Joanna; Pérez-Sánchez, Horacio (Molecules (Basel, Switzerland), 2018)
Actin functions are crucial for the ability of the cell to execute dynamic cytoskeleton reorganization and movement. Nutraceuticals that form complexes with actin and reduce its polymerization can be used in cancer therapy to prevent cell migration and metastasis of tumors. The aim of this study was to evaluate the ability of isoflavones to form complexes with actin. Docking simulation and isothermal titration calorimetry were used for this purpose. The formation of complexes by hydrogen bonds, hydrophobic and π-π interactions was demonstrated. Interactions occurred at the ATP binding site, which may limit the rotation of the actin molecule observed during polymerization and also at the site responsible for contacts during polymerization, reducing the ability of the molecule to form filaments. The greatest therapeutic potential was demonstrated by isoflavones occurring in red clover sprouts, i.e., biochanin A and formononetin, being methoxy derivatives of genistein and daidzein.